Nitrogen fixation rate of Acacia mangium Wild at mid rotation in Brazil is higher in mixed plantations with Eucalyptus grandis Hill ex Maiden than in monocultures - Paula, Ranieri R. (2018)
Key message: Inter-specific interactions with eucalypts in mixed plantations increased N2fixation rate of acacia trees compared to monocultures. N2fixation was higher during the wet summer than during the dry winter both in acacia monocultures and in mixed plantations. Context: Introducing N-fixing trees in fast-growing tropical plantations may contribute to reducing the long-term requirements of N fertilizers. Management practices established in forest monocultures should be revisited in mixed-species plantations. Aims: This field experiment aimed to compare N2 fixation rates of Acacia mangium Wild in monospecific stands and in mixed-species stands with Eucalyptus grandis W. Hill ex Maiden. A secondary objective was to gain insight into the seasonal variations of N2 fixation. Methods: 15N was applied to acacia and eucalypt monocultures and mixed-species with a 1:1 ratio at mid rotation. Leaves were collected in autumn, winter, spring, and summer to determine the foliar N concentrations and 15N atom fraction. The N content in the above-ground biomass was estimated as well as the percentage of N derived from atmospheric N2 (%Ndfa) using eucalypts in monoculture as reference plants. Results: %Ndfa values averaged over the year were 14% in monoculture and 44% in mixed-species stands. While the stocking density of acacia trees was twice as high in monoculture as in mixture, the amounts of N fixed in above-ground biomass of acacia trees were close (35–39 kg N ha−1) at 39 months after planting. %Ndfa values were higher during the wet summer than the dry winter both in acacia monocultures and in mixed plantations. Conclusion: The stocking density of acacia trees can be reduced in mixed plantations with eucalypts in comparison to acacia monocultures with a low influence on the input of N to soil through biological fixation.